2017
DOI: 10.1177/0333102417695105
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies novel susceptibility loci for migraine in Han Chinese resided in Taiwan

Abstract: Background Susceptibility genes for migraine, despite it being a highly prevalent and disabling neurological disorder, have not been analyzed in Asians by genome-wide association study (GWAS). Methods We conducted a two-stage case-control GWAS to identify susceptibility genes for migraine without aura in Han Chinese residing in Taiwan. In the discovery stage, we genotyped 1005 clinic-based Taiwanese migraine patients and 1053 population-based sex-matched controls using Axiom Genome-Wide CHB Array. In the repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…Migraine with aura (n = 52) P [31]; however, other study of the Han Chinese population failed to find a significant association between alleles, genotypes of the two SNPs (rs10166942 and rs111721132) and migraines [27].…”
Section: Control (N = 200) Migraine Without Aura (N = 148)mentioning
confidence: 89%
See 2 more Smart Citations
“…Migraine with aura (n = 52) P [31]; however, other study of the Han Chinese population failed to find a significant association between alleles, genotypes of the two SNPs (rs10166942 and rs111721132) and migraines [27].…”
Section: Control (N = 200) Migraine Without Aura (N = 148)mentioning
confidence: 89%
“…We found that rs4379368 (in c7orf10) and rs13208321 (in FHL5) were potential genetic markers for migraines in the She population [20]. In the present study, four SNPs were chosen based on their association with migraines identified in previous studies [22][23][24][25][26][27][28][29][30][31] as well as in a meta-analysis of 29 GWAS [20]. The rs2651899 SNP is localized to PRDM16, which is associated with myelodysplastic syndromes, acute myeloid leukemia and metabolic syndrome [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several single nucleotide polymorphisms (SNPs) associated with migraine susceptibility were recently identified by genome-wide association studies (GWAS) [11]. In our study among the Han Chinese population in Taiwan, several novel variants were identified to be associated with migraine in a two-stage GWAS [12], including rs655484 in disks large homolog 2 (DLG2) and rs3781545 in GDNF family receptor alpha-1 (GFRA1), rs10803531 in G protein-coupled receptor 39 (GPR39), and rs7565931 in uridine phosphorylase 2 (UPP2). Furthermore, the association between migraine and rs10166942 in transient receptor potential melastatin 8 (TRPM8) as well as rs1172113 in low density lipoprotein receptor-related protein 1 (LRP1), the two most replicated SNPs in Caucasians, were also reproduced in our study cohort.…”
Section: Introductionmentioning
confidence: 83%
“…Other investigated endophenotypes included aura and migrainous features. The candidate genes were chosen based on the findings of our previous migraine GWAS, the only published study in Asians [12]. The current study adopted a two-stage design, including discovery and replication cohorts of patients with migraine.…”
Section: Introductionmentioning
confidence: 99%